Peran Customer Involvement Dan Corporate Image Dalam Hubungan E-Wom Dengan Purchase Intention - Rahayu, Fatik (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2017)
There are many studies about the impact of e-WOM on purchase intention. Rarely studies that focus on the role of customer involvement and corporate image in the relationship between e-WOM with purchase intension especially in education context. The purposes of this study are to investigate the moderating effect of customer involvement and mediating effect of corporate image in the relationsip between e-WOM with purchase intention in higher education. The sample are students of senior high school who have ever search for opinions or reviews through the internet before choosing the university. A SEM is used to asses the relationship of the researh model. The results show that customer involvement has moderating effect and corporate image has mediating effectc in relationship between e-WOM with purchase intention. These results provide new insight into the relationship model between e-WOM with purchase intention in higher education